Implementation of Standard setting in the Assessment of Examinations in a Postgraduate Medical College: Opinions, Experiences and Prospects - Oyenike Oyeronke Ekekezie; Titilope Oyinlola Charles-Eromosele; Foluke Adenike Olatona; Emmanuel Nwabueze Aguwa (Nigerian Postgraduate Medical Journal)
Context: The world over, there has been a paradigm shift in medical education from the traditional curriculum to Competency-Based Medical Education (CBME), of which the application of standard setting in assessments is an integral part. Standard setting is the process used to define an acceptable level of performance and to establish a pass score for the defined levels of performance in the competency domains assessed by an examination. Aims: This study was designed to assess the opinions and experiences of key judges for implementation of standard setting and to outline its prospects from their perspective. Settings and Design: A descriptive cross-sectional study on the opinions, experiences and prospects for standard setting in the assessment of college examinations. Methods: A total population survey of Faculty Officers for the year 2024. Data Analysis: Descriptive statistics using SPSS Version 27. Results: The use of an arbitrary 50% pass mark was not supported as 80% of the respondents felt it was neither just nor equitable; 84% opined that it will not correctly separate competent from incompetent candidates and 76% felt it was not defensible. Over 90% of the respondents supported the shift to standard setting, though 31% and 51%, respectively, believed that it was difficult to implement and strenuous. Training and retraining of faculty and examiners was advocated by 98% of the respondents. Conclusion: Standard setting is more appropriate in determining true competence than using arbitrary pass scores. Training and retraining of faculty and examiners is required to improve understanding of the process and concepts.